2017
DOI: 10.1590/1981-6723.14416
|View full text |Cite
|
Sign up to set email alerts
|

Manejo da solução nutritiva sobre a qualidade pós-colheita de tomate salada fertirrigado em areia

Abstract: Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições desde que o trabalho original seja corretamente citado. Manejo da solução nutritiva sobre a qualidade pós-colheita de tomate salada fertirrigado em areia Management of the nutrient solution for postharvest quality of tomatoes with fertigation in sandResumo O presente trabalho teve como objetivo avaliar o efeito de manejos e concentraçõ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…Thus, the values obtained for the West Indian cherry fruits in this study (on average 10.28 ºBrix) are in accordance with the quality standard for processing and marketing the pulp. Thus, the increase in the synthesis of soluble solids in the pulp of West Indian cherry due to the greater availability of N-K is understandable, given the functions performed by these nutrients in metabolic reactions, participating in the synthesis and translocation of carbohydrates and proteins, resulting in the increase of soluble solids (Takahashi et al, 2018). Barros et al (2012) concluded that nitrogen fertilization positively influences the soluble solids contents of watermelon.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the values obtained for the West Indian cherry fruits in this study (on average 10.28 ºBrix) are in accordance with the quality standard for processing and marketing the pulp. Thus, the increase in the synthesis of soluble solids in the pulp of West Indian cherry due to the greater availability of N-K is understandable, given the functions performed by these nutrients in metabolic reactions, participating in the synthesis and translocation of carbohydrates and proteins, resulting in the increase of soluble solids (Takahashi et al, 2018). Barros et al (2012) concluded that nitrogen fertilization positively influences the soluble solids contents of watermelon.…”
Section: Resultsmentioning
confidence: 99%
“…Reductions in the FLA content of cherry tomato fruits subjected to lactic fermentation formulations and with increased ECw may be associated with delayed fruit deterioration. During the ripening process of vegetables, chlorophyll is degraded, while there is synthesis of other pigments such as flavonoids (Takahashi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect to be emphasized is the post-harvest quality, because the cherry tomato fruit has high perishability, caused by the increase in respiratory metabolism, due to the high moisture content of this vegetable, depreciating the commercial value of fruits for fresh consumption (Takahashi et al, 2018). In this context, one of the techniques that can be used for postharvest preservation in vegetables is lactic fermentation, in which bacteria, fungi, and yeasts alter the structure of foods or provide them with better taste characteristics, even extending their preservation time (Soares et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Descriptive analysis was used to compare the suitability of solutions with the limits recommended in the literature. These standards were obtained through a bibliographic survey on the nutritional requirement of tomato crops (Fernandes et al, 2002;Moraes, 1997;Pires et al, 2009;Santos et al, 2017;Takahashi et al, 2018), as shown in Table 1. These limits correspond to the maximum and minimum absolute values among the recommendations found.…”
Section: Methodsmentioning
confidence: 99%